Estrus response in dairy cows surviving foot and mouth disease given Superbooster and Immunobooster - Zulfanisa, Rizky Asrin; Rahmi Sugihartuti; Jola Rahmahani; Mohammad Anam Al Arif; Tita Damayanti Lestari; Ali Agus; Mohammad Sofi’ul Anam (Ovozoa: Journal of Animal Reproduction, 2024)
This study aims to determine the effect of adding Superbooster and Immunobooster on the estrus response of dairy cows after foot and mouth disease (FMD) infection. This study used 18 dairy cows that recovered from FMD based on veterinarian examination. Cows were divided into three groups (T0, T1 and T2). In the control group (T0), cows were fed standard feed. Standard feed consisted of forage (10% of body weight, daily) and concentrate. In the T1 group, cows were fed standard feed added with Superbooster (40 g daily), and in the T2 group cows were fed standard feed added with Superbooster (40 g daily) and Immunobooster (800 g daily). This treatment was carried out for 42 days. The results showed that the estrus rate in T1 and T2 were both 100%, which was higher compared to the control (16.67%). The onset of estrus was shorter (p <0.05) compared to the duration of the last estrus until the start of treatment. Meanwhile, the duration of the last estrus until the day of treatment and onset of estrus between treatment groups were not significantly different (p <0.05). It could be concluded that Superbooster and Immunobooster could stimulate estrus on dairy cows after FMD.